Spontaneous coronary artery dissection: a neglected cause of acute myocardial ischaemia and sudden death. Issue 5 (May 1996) - Basso, C.; Morgagni, G. L.; Thiene, G.
Abstract : Spontaneous coronary artery dissection is a rare cause of acute myocardial ischaemia. Eight consecutive fatal cases which occurred in women aged 34-54 years (mean 43) are described. The dissection involved the left anterior descending coronary artery in four, the left main trunk in two, the right coronary artery in one, and both left anterior descending and circumflex arteries in one. The clinical presentation was sudden death in six cases, and acute myocardial infarction in two. Diagnosis was made at necropsy in every case but one, in which coronary dissection was diagnosed during life by selective coronary angiography. The only ascertained risk factor was hypertension in one patient; none of the women was in the puerperium, and Marfan syndrome was excluded in all. Histology showed a haematoma between the coronary tunica media and adventitia, that flattened and occluded the lumen; a coronary intimal tear was detected in only two cases. Unusual histological findings were cystic medial necrosis in one case, eosinophilic inflammatory infiltrates in four, and angiomatosis of the tunica adventitia in one. Patients dying of spontaneous coronary dissection are usually middle aged women, with no coronary atherosclerosis and apparently no risk factors. Spontaneous coronary artery dissection is unpredictable, and sudden death is the usual mode of clinical presentation. Prompt diagnosis and life saving treatment is far from being achieved.